Notas e descrições de novos táxons em Cerambycinae Neotropicais (Coleoptera, Cerambycidae) - Napp, Dilma Solange; Martins, Ubirajara R. (Papéis Avulsos de Zoologia, 2006)
Notes and descriptions of new taxa of Neotropical Cerambycinae (Coleoptera, Cerambycidae). New taxa described: in Ectenessini: Ectenessidia metallica sp. nov. from Brazil (Distrito Federal); in Compsocerini: Upindauara gen. nov., type species U. bella sp. nov. from Brazil (Rondônia) and Goatacara gen. nov., type species, G. boliviana sp. nov. from Bolivia (Santa Cruz); in Heteropsini: Amoaba gen. nov., type species A. plumosa sp. nov. from Ecuador (Pichincha); Chrysoprasis rubricollis sp. nov. from Panama (Panama); in Rhopalophorini, Cycnoderus (C.) expeditus Chevrolat, 1859 is redescribed and recorded from Ecuador (Loja), Cycnoderus (C.) intinctus (Pascoe, 1866) comb. nov. is reinstated and Gurubira apicalis (Fuchs, 1966), comb. nov. is redescribed and illustrated.